(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the clinical efficacy, bacterial control ability, and the molecular mechanisms underlying the wound healing effects of Berberin nano gel compared with Silver Sulfadiazine 1% cream (SSD 1%) on superficial thermal burns in pediatric patients. Methods: A prospective, controlled, within-patient (split-wound) study in 34 children with II-III degree burns treated at Le Huu Trac National Burn Hospital. Each child had two damaged zones that were equivalent: Zone A was treated with Berberine nano gel, and Zone B was treated with SSD 1%. Evaluation of complete healing time, time to 50% epithelialization, surface bacterial load (D0, D7, D14), and CHEOPS pain score. Results: Time to complete healing was shortened with Berberine nano gel: superficial second-degree 8.26 ± 2.45 days vs. 9.71 ± 2.95 days; third-degree 14.85 ± 5.20 days vs. 18.41 ± 6.56 days (p <0.05). The bacterial load was reduced in both zones over time. At D7, it was significantly lower in the Berberine nano gel group (43.22 ± 37.28 vs. 92.59 ± 81.14 CFU units; p <0.05), whereas at D14 the difference was not significant. The drug was well tolerated, with a mean CHEOPS of 1.56 ± 1.56. Conclusion: Berberine nano gel shortens wound healing time, improves early bacterial control, and is a potential alternative to 1% SSD for the treatment of superficial burns in children.